Máquinas automágicas: trabalho, mente estendida e subjetividade sob o fetiche da mercadoria - Gonçalves, Luis Henrique do Nascimento (2023)
In this integrative review of scientific literature, which is exploratory and qualitative in nature, we start from the phenomenal appearance of extended mind products (digital technologies) in search of their concrete, multidetermined and contradictory reality. To do this, we reviewed digital marketing, interface design, and user experience manuals, as well as academic literature in Human-Computer Interaction, behavioral and cognitive psychology, and behavioral economics. With this, we traced deeper determinations and contradictions, which led us to study the scientific literature of the sociology of technologies, certain elements of computing (such as artificial intelligence, big data, and predictive analysis, among others), and the political economy of information and communication technologies (which includes the so-called attention economy). We demonstrate that all these elements exist as a totality, which in turn mediates other human-social determinations and contradictions that are even more profound. To reach these, we reviewed parts of the literature on epistemology, philosophy of science, the critique of political economy, the ontology of social being, as well as various approaches to the study of consciousness – especially cognitive sciences, neuroscience, paleoanthropology, and socio-historical psychology. The set of these reviews points to the referred totality as a new other link of causalities and mediations that seek to realize and reproduce the onto-negative social relations of appropriation without work, the complex of capitalist alienation, and its structural crisis of profitability. For this totality to move and thus exist, extended mind products create and mediate needs that can only be partially satisfied and in the form of a false simple exchange, where, in the act of consumption, their users ultimately work and act as productive and/or reproductive forces of capital. Through corporate secrets, alleged computational inexplicabilities, and the fetish of the commodity, all these determinations and contradictions are "encrypted" in algorithms, interfaces, and user experiences and their rewards. All this detour allows us to return to the surface of extended mind products now aware of their concrete existence, which, however, appears fetishized as automagical machines. This allows us to better understand that the enchantment and dependency that these products cause are, to a large extent, phenomena related to estrangement (Entfremdung). For all these reasons, we conclude that these mystifications and their confrontation are new other forms of class struggle, and that new interdisciplinary studies are necessary to understand and transform this reality